PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD (STUDENT TEAMS ACHIEVEMENT DEVISIONS) DENGAN PEMBELAJARAN KONVENSIONAL PADA MATERI TERMOKIMIA KELAS XI SMA NEGERI 7 PALU - Rusli, Riana A.; Sabang, Sri Mulyani; Tangkas, I Made (Jurnal Akademika Kimia, 2013)
The aims of this research is to increase result of learning student at items of thermochemistry of class XI SMA Negeri 7 Palu. One of effort used to increase result of learning the by applying model the study of co-operative of type STAD (Student Teams Achievement Devision). As for which this research background because items termokimia represent the items assumed difficult by this items and student also of vital importance comprehended by student of class XI. So that is not assumed difficult, draging on and is easy to comprehended by student hence teacher have to give a pleasant study model with the model of study of co-operative of type STAD (Student Teams Achievement Devision). this Research Population is all student of class of XI IPA SMA Negeri 7 Palu of school year 2012/2013 consisted of by 3 class and sampel used consisted of by two class that is XI IPA1 as much 37 people as class of experiment and class of XI IPA2 as much 37 people as control class determined by purposive sampling. Data collecting done to use the instrument tes in the form of tes result of learning is tested by the student chemistry of validity, reliabilitas, mount the difficulty and energy of the difference. Data examination result of research use the statistical analysis test the t one party (right) with the prerequisite test, test the normalitas, and homogeneity. At this research obtained by a mean score result of learning student by using model of study of co-operative of type STAD is 13.20 while mean score result of learning student following conventiona l study 8.93. Pursuant to hypothesis examination statistically test the t one party (right) obtained by value t calc > t table that is 6.88 > 1.67 with the belief level = 0.05 and dk = 72. The result refer that result learn the student chemistry use the model of study of compared to by better type STAD co-operative result learn the student by using conventional study model.